2018
DOI: 10.1088/0256-307x/35/7/070201
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Soliton Solutions for the Coupled Fokas–Lenells System via Riemann–Hilbert Approach

Abstract: We aim to construct multi-soliton solutions for the coupled Fokas–Lenells system which arises as a model for describing the nonlinear pulse propagation in optical fibers. Starting from the spectral analysis of the Lax pair, a Riemann–Hilbert problem is presented. Then in the framework of the Riemann–Hilbert problem corresponding to the reflectionless case, N-soliton solutions to the coupled Fokas–Lenells system are derived explicitly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Constructing Jacobi elliptic doubly periodic solutions of nonlinear PDEs with fractional derivatives is worthy of the study. At the same time, constructing multisoliton solutions via the Riemann-Hilbert approach, for example, see Kang et al's meaningful work [52,53], has been a hot topic. Dealing with initial-boundary problems of nonlinear PDEs by means of the Riemann-Hilbert approach is also worthy of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing Jacobi elliptic doubly periodic solutions of nonlinear PDEs with fractional derivatives is worthy of the study. At the same time, constructing multisoliton solutions via the Riemann-Hilbert approach, for example, see Kang et al's meaningful work [52,53], has been a hot topic. Dealing with initial-boundary problems of nonlinear PDEs by means of the Riemann-Hilbert approach is also worthy of the study.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5, the spatial structures of solutions (27) determined by (52) are shown by selecting the parameters as a 0 = 2, A 0 = 0 5, c 0 = −4, c 1 = 3, c 2 = −1, k = 1 5, and m = 0 8, respectively. We shown the spatial structures of solutions (40) in Figure 6.…”
Section: Singular Nonlinear Dynamicsmentioning
confidence: 99%
“…Constructing exact solutions of nonlinear mathematical physical equations is of theoretical and practical significance. Since the famous Korteweg-de Vries (KdV) equation was solved in 1967 [7], a large number of exact solutions like [2][3][4][5][6][7]10,11,[13][14][15][16][18][19][20][22][23][24][25][26][27][28]31,33,34,36,38,41,43] of nonlinear partial differential equations (PDEs) have been found. The exp-function method [10] proposed by He and Wu has been widely used for constructing exact solutions of nonlinear PDEs.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] multi-Hamiltonian structure and infinitely many conservation laws were established for the vector Kaup-Newell hierarchy of the positive and negative orders. Some other methods, such as Darboux transformation method [5,[8][9][10], Hirota bilinear method [11][12][13], Riemann-Hilbert problem [14][15][16], Bäcklund transformation [17] and trial equation method [18] could be found in references.…”
Section: Introductionmentioning
confidence: 99%